Clinical interpretation of antineutrophil cytoplasmic antibodies: parvovirus B19 infection as a pitfall. Issue 4 (14th October 2004) - Hermann, J; Demel, U; Stünzner, D; Daghofer, E; Tilz, G; Graninger, W
Abstract : Background: While antibodies directed against proteinase 3 (PR3-ANCA) and myeloperoxidase (MPO-ANCA) have a high specificity for the diagnosis of systemic vasculitis, they may also be found as an epiphenomenon of acute viral infection. Objective: To investigate whether positive ANCA test results may be a common feature of acute parvovirus B19 infection. Methods: Sera were analysed from 1242 patients from a rheumatology outpatient clinic for reactivity with parvovirus B19 and EBV antibodies. They were tested for the presence of PR3-ANCA and MPO-ANCA, along with sera known to contain IgM antibodies to these viruses obtained from among 41 366 samples submitted for virological screening. Results: ANCA were found in 10% (5/50) of the sera positive for IgM antibodies to parvovirus and in 3/51 sera containing IgM antibodies to EBV. Three of six patients with arthritis and concomitant parvovirus infection were found positive for PR3-ANCA and two were found positive for MPO-ANCA. All six patients tested negative for ANCA after six months of follow up. Conclusions: PR3-ANCA and MPO-ANCA may occur transiently in patients with acute B19 infection or infectious mononucleosis, highlighting the importance of repeated antibody tests in oligosymptomatic clinical conditions in which systemic autoimmune disease is suspected.